PEMBANGUNAN APLIKASI PENGENALAN VAKSIN COVID-19 BERBASIS AUGMENTED REALITY PADA RS EFARINA ETAHAM - M Tuahoryanda Tarigan; Haida Dafitri; Septiana Dewi Andriana (JISTech (Journal of Islamic Science and Technology), 2022)
Efarina Etaham Hospital provides Covid-19 vaccination services for the community. One of the factors that influence people not to vaccinate is the lack of knowledge or education about the vaccination process. This is proven by the fact that there are still many people in the Efarina Etaham Hospital environment who have not carried out vaccinations. For this reason, this research will provide solutions to solve these problems by utilizing technology. The need for education regarding the importance of vaccination will be poured into applications based on augmented reality. This application will display vaccine introduction, information on the Covid-19 vaccine, and how the vaccine works in the human body.